A REVIEW OF DIGITAL TECHNOLOGY FOR TRANSFORMATION OF VOCATIONAL AND TECHNICAL EDUCATION (NAU Journal of Technology and Vocational Education, 2026)
In recent years, the integration of digital technologies into vocational and technical education (VTE) has become a key driver for improving learning outcomes, closing skills gaps, and promoting equity and access. This review explores current studies and practices involving the use of digital tools—including augmented and virtual reality, simulation software, e-learning platforms, mobile applications, cloud services, and Internet of Things (IoT) devices—and evaluates their influence on pedagogy, learner engagement, instructor roles, and institutional capacity. This review highlights on the concepts of vocational and technical education (VTE), digital technology and educational transformation. It further highlights on the theories guiding the study, types of digital technologies used in VTE, their roles and benefits, challenges and need for transformation and purposes. The review also recommends future research needs such as long-term impact assessments, cost–benefit studies, and investigations into emerging innovations like artificial intelligence and immersive virtual environments to further improve the effectiveness and scalability of VTE across varied socio-economic settings and conclusion.
Keywords: Digital technologies; vocational and technical education; Technical and vocational Education and Training